Tailoring the structure of Kevlar nanofiber and its effects on the mechanical property and thermal stability of carboxylated acrylonitrile butadiene rubber. Issue 26 (12th March 2019) - Xue, Xiaodong; Jiang, Kuan; Yin, Qing; Zhang, Xumin; Zhang, Wanqi; Jia, Hongbing; Ji, Qingmin
ABSTRACT: Water‐dispersible hydrolyzed Kevlar nanofibers (hANFs) prepared by acid‐assisted hydrothermal treatments of Kevlar nanofibers (ANFs) were first incorporated into carboxylated acrylonitrile butadiene rubber (XNBR) by a latex co‐coagulation method. The obtained hANFs maintained the one‐dimensional nanofibrous morphology and crystal structure as ANFs. There were amounts of polar groups appearing at the end of hANFs molecular chains after hydrothermal process, which led to the strong hydrogen bonding interaction between the filler and XNBR matrix. The results indicated that hANFs had significant reinforcement effects on the mechanical properties, crosslink density, and thermal stability of XNBR matrix. In comparison with those of neat XNBR, the tensile strength, tear strength, crosslink density, and maximum heat decomposition temperature ( T max ) of XNBR/hANFs nanocomposites filled with 7 phr hANFs increased by 236%, 161%, 35%, and 19.64 °C, respectively. © 2019 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2019, 136, 47698. Abstract : Water‐dispersible hydrolyzed Kevlar nanofibers with large amounts of polar groups will have good dispersibility in carboxylated acrylonitrile butadiene rubber matrix as well as better interaction with the matrix via hydrogen bonding.